Sistem Penunjang Keputusan Untuk Penanganan Penderita Gagal Jantung - Sutedjo, Eddy; Trisnawarman, Dedi; Hartanto, Ferdinand (Bina Nusantara University, 2010)
Technology is one important factor that supports accuracy result of a disease in health. Along with technology, one?s knowledge could be broadening so he can make one exact decision about specific disease to get maximal result. Based on above considerations, it is designed a supporting decision-making system based on entered data, processed using weighting in AHP to know the result. The programming language is using PHP and the database using MySQL. The designing result could help doctors to choose specific medicine for the patients and help them to find information about cardiac failure and what stages to be done to help the patients healing.